The use of game-based learning in English class - Ahmad Ghazy; Majid Wajdi; Clary Sada; Ikhsanudin Ikhsanudin (English, 2021)
English teachers may come across challenges within the process of English language teaching, especially now, when technologies and innovations grow rapidly. Teachers who trapped in traditional comfort zone of teaching might left behind. Nevertheless, an English teacher of Sekolah Tunas Bangsa is familiar with new technological media by applying Game-Based Learning to teach English in the classroom. This research aims to explore the using of GBL to increase students’ interest in learning English. This research was conducted in Primary level of Sekolah Tunas Bangsa where an English teacher became the focused participant of this study. The Narrative Inquiry method was used to conduct this research by following the research procedure taken from Creswell (2012). The findings show that the teacher used some game-based platforms, such as Kahoot!, Quizizz, ESL Games Plus, and Duolingo, because they are rich of visuals and easy to play. In this study, the teacher conducted GBL by using structured schedule consisted of instruction, presentation, and reflection helped the students to engage with the materials being learnt. The way the teacher managed the using of GBL by following a structured schedule has also promoted fun and interesting learning. Then, the teacher’s reason on using GBL in the classroom was exposed as her way to engage and to motivate the students in learning English. She believes that when the students feel challenged as well as having fun during the learning, the level of interest increases. The students’ achievements have also increased when the teacher uses GBL in the classroom. In conclusion, the using of GBL has successfully increased the students’ interest in learning English.